Oral Health Related Quality of Life in Geriatric Patients - A Review - Chetan Modgi,; Usha Radke, (Journal of Orofacial Research, 2021)
Health is defined by WHO as; not only the absence of disease but a multidimensional construct that also includes subjective parameters of well-being. Oral health has a strong biological, psychological and social consequence as it affects aesthetics, communication, and quality of life. Oral health-related quality of life (OHRQOL) is a relatively new, but rapidly growing phenomenon. OHRQOL is associated with: Functional factors, psychological factors, social factors, and experience of pain or discomfort. Complete tooth loss or being completely edentulous signifies death in dental well-being constituting a common and irreversible health problem in the elderly. Oral health-related quality of life (OHRQoL) is one of the key aspects of the health of geriatric health.